2019
DOI: 10.1177/2516043519869447
|View full text |Cite
|
Sign up to set email alerts
|

Identifying quality improvement opportunities using patient complaints: Feasibility of using a complaints taxonomy in a metropolitan maternity service

Abstract: Background: The Healthcare Complaints Analysis Tool (HCAT) is a coding taxonomy developed to interrogate patient complaints for quality and safety improvement lessons. The reliability of the tool has been tested in whole-of-system and whole-of-service settings. We sought to assess whether the taxonomy is functional at the level of a single hospital department. Objectives: To demonstrate the feasibility of applying HCAT in the setting of a large maternity department with a view to using it to inform quality and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 61 publications
(135 reference statements)
2
6
0
Order By: Relevance
“…Of all the compliments received by the health service in a 12‐month period, only 15% ( n = 422) were specific to nursing or midwifery care, and of these only 7.9% ( n = 225) were provided by healthcare consumers (i.e., patients and family or companions). Similar proportions were reported in an Australian study that examined 200 complaints and identified approximately 17.5% (35 of 200) of these related to clinical nursing care (Nowotny, Loh, Davies‐Tuck, et al, 2019). Further comparison is difficult as the authors did not identify the source of the complaints (e.g., consumers or others) or provide sufficient detail to examine nursing‐specific findings.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Of all the compliments received by the health service in a 12‐month period, only 15% ( n = 422) were specific to nursing or midwifery care, and of these only 7.9% ( n = 225) were provided by healthcare consumers (i.e., patients and family or companions). Similar proportions were reported in an Australian study that examined 200 complaints and identified approximately 17.5% (35 of 200) of these related to clinical nursing care (Nowotny, Loh, Davies‐Tuck, et al, 2019). Further comparison is difficult as the authors did not identify the source of the complaints (e.g., consumers or others) or provide sufficient detail to examine nursing‐specific findings.…”
Section: Discussionsupporting
confidence: 76%
“…Similar proportions were reported in an Australian study that examined 200 complaints and identified approximately 17.5% (35 of 200) of these related to clinical nursing care (Nowotny, Loh, Davies-Tuck, et al, 2019). Further comparison is difficult as the authors did not identify the source of the complaints (e.g., consumers or others) or provide sufficient detail to examine nursing-specific findings.…”
Section: Discussionmentioning
confidence: 53%
“…There are several strengths to this study. Firstly, the HCAT is a valid and reliable tool which has been applied successfully to many different healthcare settings [ 23 , 25 , 39 , 40 ]. The agreement between raters in this study indicated that the HCAT was a suitable tool for the analysis of complaints made about this Irish hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Complaints have been analysed in both hospital [23][24][25]] and primary care [26] settings in Ireland prior to the COVID-19 pandemic. However, it is not known if, and how, the COVID-19 pandemic may have impacted complaints.…”
Section: Introductionmentioning
confidence: 99%
“…Cossler and colleagues describe an innovative use of their hospital’s malpractice data to identify risks to the safety of obstetric patients and their newborns. 5 Using these data they identified four key drivers of malpractice risk. Armed with this information, they created a regional obstetric quality network which intervened to reduce those risks.…”
mentioning
confidence: 99%